Efficacy of Plantago major Homoeopathic Mother Tincture as Mouth Wash in Comparison with Chlorhexidine Gluconate (0.2%) Mouthwash in Management of Oral Hygiene among Students: A Double-Blind, Parallel-group, Randomized Control Trial - Kunal Deshmukh; Sahana Hegde Shetiya; Parth Aphale; Anindita Dutta; Dharmendra B. Sharma; Garvit Singh (Journal of Indian Association of Public Health Dentistry)
Background: Plantago major (P. major) has anti-inflammatory, antimicrobial, and wound-healing properties. It also augments the production of nitric oxide which plays a role in protecting the gingival tissues against infection. Objective: The present study was carried out to assess and compare the efficacy of P. major homeopathic mother tincture as mouthwash with 0.2% chlorhexidine gluconate (CHX) mouthwash for the treatment of gingivitis. Materials and Methods: A double-blind, randomized controlled parallel trial was conducted for 1 month. Sixty participants (15 males and 45 females) aged 18–22 years were randomly allocated into two groups by computer-generated random number; Group A: CHX gluconate 0.2% and Group B: P. major (mother tincture). Gingival index (GI) and plaque index (PI) were assessed by modified GI and Quigley-Hein PI at baseline and postintervention. Results: Mean rank and difference in GI and PI within the intervention group from baseline to 30 days were calculated using the Wilcoxon signed-rank test and paired t-test which was statistically significant (P < 0.001). However, there was no statistical significance between the P. major and CHX group postintervention for PI and GI. Conclusion: The double-blind trial conducted to confirm the anti-inflammatory properties of P. major mouthwash has shown efficacy in reducing both PI and GI from baseline to 30 days. However, there was no significant difference in GI and PI between the CHX mouthwash (0.2%) and P. major mouthwash group at the end of the trial.